2013
DOI: 10.1177/0363546513489262
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex on the Outcome of Autologous Chondrocyte Implantation in Chondral Defects of the Knee

Abstract: Autologous chondrocyte implantation is a promising treatment option for full-thickness cartilage defects of male and female knee joints. Female patients with patellar defects have worse prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 46 publications
7
59
1
Order By: Relevance
“…Donor samples differed in age and gender but there were no obvious indications that this affected the potency of spheroids and confirmed observations in clinical practice where no significant differences in regeneration of condyle defects in male and female donors was observed [24]. The newly formed tissue mainly consisted of homogenous distributed cells filling up the defect, which was covered by a multi/monolayer of elongated cells arranged parallel to the surface with a smooth appearance attached to the surface of the native cartilage tissue.…”
Section: Discussionsupporting
confidence: 79%
“…Donor samples differed in age and gender but there were no obvious indications that this affected the potency of spheroids and confirmed observations in clinical practice where no significant differences in regeneration of condyle defects in male and female donors was observed [24]. The newly formed tissue mainly consisted of homogenous distributed cells filling up the defect, which was covered by a multi/monolayer of elongated cells arranged parallel to the surface with a smooth appearance attached to the surface of the native cartilage tissue.…”
Section: Discussionsupporting
confidence: 79%
“…The present population consisted of 565 patients. In concordance with the present study, Kreuz et al [25] recently found a (somewhat smaller) gender difference in Lysholm score both before and after autogenous chondrocyte implantation in 52 patients. Briggs et al [8] did not find a gender difference in 488 healthy subjects without knee problems.…”
Section: Discussionsupporting
confidence: 93%
“…Autologous chondrocyte implantation (ACI) in the knee joint using a periosteal flap [1] has become a promising treatment with encouraging results for femoral and patellar cartilage defects [2][3][4][5][6]. In the last two decades since the first study by Brittberg et al, its further developments including the third generation autologous chondrocyte implantation using collagen I/III scaffolds has become increasingly popular for treatment of large full thickness cartilage defects.…”
Section: Introductionmentioning
confidence: 99%